They shoot horses don't they? - Winkler, Irwin; Chartoff, Robert; Pollack, Sydney 1934-2008; Fonda, Jane 1937-; Sarrazin, Michael 1940-2011; York, Susannah 1939-2011 (MGM DVD, 2004)
In the midst of the Depression, an entire generation sought out the dance marathon as a means of survival. Gig Young won an Oscar for Best Supporting Actor as the contest promoter